Antibiofilm efficacy of plant extracts as root canal irrigants in endodontics: a systematic literature review - Diouchi, Jihad; Touré, Babacar; Ghoul, Sonia (Frontiers in Dental Medicine, 2024)
Background: To explore the antibiofilm efficacy of plant extracts against in vitro formed single and multispecies endodontic biofilms, in comparison to conventional root canal irrigants.Methods: PubMed, Scopus, Web of Science, and EMBASE were searched up to April 2024. Studies investigating the antibiofilm efficacy, of at least one plant extract and one conventional root canal irrigant, against endodontic biofilms were reviewed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement guidelines. Data were extracted, and studies were critically assessed using the Joanna Briggs Institute checklist. Results: Among 78 articles, eight articles met the criteria and were eventually included in this review. One study showed a high risk of bias, six showed a moderate risk of bias, and one showed a low risk. A total of twelve plant extracts were tested for their antibiofilm efficacy against eight different single-species biofilms and one multispecies biofilm. A combination of microscopy methods and culturing techniques was used for the assessment of their efficacies. Plant extracts exhibited either a biofilm disruption and/or inhibition of biofilm formation. Psidium cattleianum extract and Psidium guajava exhibited enhanced efficacy compared to Chlorhexidine and NaOCl, respectively. Allium sativum demonstrated comparable efficacy to NaOCl. Furthermore, the combination of Cymbopogon martinii essential oil and NaOCl was found to be more effective than either alone when tested on a multispecies biofilm. However, the other plant extracts, such as Mikania Sprengel, Salvadora persica, Camellia sinensis, and Vitis vinifera showed efficacy but were still inferior compared to the control group. Conclusions: Overall, the tested plant extracts demonstrated promising potential for combating in vitro endodontic biofilms. In that context, integrating conventional therapy protocols with plant inspired treatments may allow effective endodontic biofilm eradication. Hence, future research should focus on optimizing the synergistic combinations of these extracts with NaOCl to maximize the therapeutic outcomes. Heterogeneity amongst the studies prevented a meta-analysis.